Issues of Elderly People in Nepal: A general Review (Research Nepal Journal of Development Studies, 2021)
The issues of elderly people in Nepal are different in nature. The main objective of the study is to collect and identify the different types of issues of old-age people. Normally the issues or problems related to elderly are divided in five categories i.e., cultural, economic, health, psychological, and social. It is the general review of listed references to collect and identify the issues of senior citizen. A caretaker or old age home manager must be able to address all such issues while working with old-age people. It is necessary to maintain cordial relations with old age people. To manage the disorders, we need highly sophisticated old age homes all over the country. Governments should pay more social security to inject money in market and make happy elderly friendly society. It can contribute gender equality as well.